Impact of vitamin D insufficiency on insulin homeostasis and beta cell function in nondiabetic male HIV‐infected patients. Issue 9 (8th May 2013) - Moreno‐Pérez, O; Portilla, J; Escoín, C; Alfayate, R; Reus, S; Merino, E; Boix, V; Bernabeu, A; Giner, L; Mauri, M; Sánchez‐Paya, J; Picó, A
<x xml:space="preserve">Abstract</x> Objectives Vitamin D is thought to play a role in glucose homeostasis and beta cell function. Our aim was to examine the impact of plasma 25‐hydroxyvitamin D [25(OH)D] upon in vivo insulin sensitivity and beta cell function in HIV‐infected male patients without diabetes. Methods A cross‐sectional study was carried out involving a cohort of HIV‐infected patients undergoing regular assessment in a tertiary hospital. Eighty‐nine patients [mean (± standard deviation) age 42 ± 8 years] were included in the study: 14 patients were antiretroviral therapy (ART)‐naïve, while 75 were on ART. Vitamin D insufficiency (VDI) was defined as 25(OH)D < 75 nmol/L; insulin sensitivity was determined using a 2‐h continuous infusion of glucose model assessment with homeostasis (CIGMA‐HOMA), using the trapezoidal model to calculate the incremental insulin and glucose areas under the curve (AUCins and AUGglu, respectively). Beta cell function was assessed using the disposition index (DI). Abdominal visceral adipose tissue (VAT) and hepatic triglyceride content (HTGC) were measured by magnetic resonance imaging (MRI) and 1‐H magnetic resonance spectroscopy. Multivariate linear regression analysis was performed. Results VDI was associated with insulin resistance (IR), as indicated by a higher CIGMA‐HOMA index (odds ratio 1.1) [1.01–1.2]. This association was independent of the main confounders, such as age, Centers for Disease Control and Prevention (CDC) stage, ART, lipodystrophy, body mass index, VAT:subcutaneous adipose tissue ratio and HTGC, as confirmed by multivariate analysis (B = 12.3; P = 0.01; r2 = 0.7). IR in patients with VDI was compensated by an increase in insulin response. However, beta cell function was lower in the VDI subpopulation (33% decrease in DI). Conclusions VDI in nondiabetic HIV‐positive male patients is associated with impaired insulin sensitivity and a decrease in pancreatic beta cell function.